Normative Shifts in the Global Conception of Climate Change: The Growth of Climate Justice - Evan Gach (Social Sciences, 2019)
While climate change has been framed as an environmental issue from the very beginning of United Nations Framework Convention on Climate Change (UNFCCC) negotiations, over the years the concept has expanded to further emphasize it as a fundamental issue of human rights and global justice. This paper examines the evolution of the conception of climate change since 2009, arguing that the issue framing utilized by UNFCCC member states has increasingly trended toward some aspects of the climate justice frame, including disparities in vulnerability to climate change (loss and damage), human rights impacts, and social inequalities. This shift also extends to the framing adopted by civil society organizations in the form of the Climate Action Network (CAN International), in which a larger focus on issues of climate justice can be seen in recent years. These trends are then reviewed alongside the objectives, mechanisms, and language of the ratified text of the Paris Agreement in order to evaluate the status of the growing international norm of climate justice.